2019
DOI: 10.1080/24749508.2019.1585658
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effects on landscape and environment in glacierized Alpine areas: retreating glaciers and enlarging forelands in the Bernina group (Italy) in the period 1954–2007

Abstract: We analysed the recent involution of glaciers in the Bernina group (Italy), which are shrinking thus permitting a rapid enlargement of the forelands. We delimited glacier outlines upon aerial photographs (1954 and 1981 stereo pairs analysed through an optical system) and orthophotos (2003 and 2007 digital imagines directly managed via GIS software). All the obtained data were overlapped and compared. The estimated glacier area change during 1954-2007 was −36.5 ± 2.4% (−16.2 ± 0.4 km 2). The changes sped up mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 110 publications
0
15
0
Order By: Relevance
“…In fact, essential abiotic ecosystem services for human activities are being severely impacted by the ongoing changes [93]. The effects of the ongoing deglaciations are well perceptible along this kind of trail, where the recolonization of vegetation characterizes increasingly widening proglacial areas [127], where geosites are affected by paraglacial-type transformation [94]. Therefore, the availability of high altitude geotrails represents a strength in areas such as the SVUGG, for bringing attention to the abiotic ecosystem services (sensu Gray [8]).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, essential abiotic ecosystem services for human activities are being severely impacted by the ongoing changes [93]. The effects of the ongoing deglaciations are well perceptible along this kind of trail, where the recolonization of vegetation characterizes increasingly widening proglacial areas [127], where geosites are affected by paraglacial-type transformation [94]. Therefore, the availability of high altitude geotrails represents a strength in areas such as the SVUGG, for bringing attention to the abiotic ecosystem services (sensu Gray [8]).…”
Section: Discussionmentioning
confidence: 99%
“…Trees in glacier forefields typically grow on initial and very young soils formed on glacial deposits and till. These recently deglaciated areas at elevations below the plant species' limit and below the treeline-which is the case for most of the large valley glaciers in the Alps, including our study site -typically undergo primary successions and forest invasion (Huggett 1998;Walker et al 2010;Garbarino et al 2010;D'Amico et al 2015;D'Agata et al 2019).…”
Section: Introductionmentioning
confidence: 90%
“…The fruit is rich in flavonoids, anthocyanins and polyphenols, aronia melanocarpa fruit and its extracts have good biological activity in antioxidant, anti-inflammatory, anti-cancer, lowering blood sugar, effects in the treatment of heart disease, hypertension and other cardiovascular and cerebrovascular diseases, which have broad prospects for development, but the relevant aronia melanocarpa salt tolerance physiological research has not been reported. The real data information on how to get the effective aronia melanocarpa under saline alkali stress condition has become a hot topic in recent years (Brzska and Rogalska, 2016), (D'Agata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%